Preparation method of sodium-doped coal-based yellow fluorescent carbon dots

Sodium-doped coal-based yellow fluorescent carbon dots were prepared by pretreatment of bituminous coal and hydraulic cavitation technology. This solved the problem that the fluorescence of existing coal-based carbon dots is concentrated in the short wavelength range, and achieved the acquisition of yellow fluorescence and improved biocompatibility. It is suitable for flexible quantum dot displays and warm white LED light sources.

CN120865891AActive Publication Date: 2025-10-31CHINA UNIV OF MINING & TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202511264724.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-05
Publication Date
2025-10-31
Estimated Expiration
2045-09-05

AI Technical Summary

Technical Problem

The fluorescence of existing coal-based carbon dots is mainly concentrated in the short-wavelength region, which leads to damage to biological tissues and limits their application potential in fields such as optoelectronic devices and biological imaging.

Method used

Bituminous coal was pretreated with a mixed solution of concentrated nitric acid, hydrogen peroxide and sodium hydroxide. Combined with hydraulic cavitation technology, graphite microcrystals were exfoliated to form sodium-doped coal-based yellow fluorescent carbon dots, while retaining surface groups and altering the band structure.

Benefits of technology

The fabrication of yellow fluorescent carbon dots expands the color gamut, avoids damage to biological tissues from short-wave radiation, meets the needs of flexible quantum dot displays and warm white LED light sources, and is also low-cost and environmentally friendly, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120865891A_ABST
    Figure CN120865891A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of sodium-doped coal-based yellow fluorescent carbon dots, and belongs to the technical field of coal-based carbon nanomaterials. The preparation method of the sodium-doped coal-based yellow fluorescent carbon dots comprises the following steps: adding bituminous coal into a mixed solution of concentrated nitric acid and hydrogen peroxide, carrying out a first mixing reaction, adding sodium hydroxide, adjusting the pH value to be neutral, and carrying out a second mixing reaction to obtain a coal sample; a coal sample is added into water to prepare a bituminous coal mixed solution, then the bituminous coal mixed solution is subjected to cavitation stripping treatment, and the sodium-doped coal-based yellow fluorescent carbon dots are obtained. The coal-based carbon dots with yellow fluorescence are prepared, the bottleneck that the fluorescence of the coal-based carbon dots is generally blue is broken through, the fluorescence wavelength of the coal-based carbon dots is prolonged, damage of short-wave radiation to biological tissues is avoided, the color gamut range of the coal-based carbon dots is expanded, and the application range of the coal-based carbon dots is widened. And the fluorescent requirements of flexible quantum dot display, a warm-color white LED light source, full-spectrum catalysis and the like on long wavelength are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coal-based carbon nanomaterials technology, and in particular to a method for preparing sodium-doped coal-based yellow fluorescent carbon dots. Background Technology

[0002] Carbon dots are zero-dimensional carbon particles with a size of less than 10 nm. They are generally composed of conjugated graphitic carbon cores and amorphous surface groups of various types. They possess excellent optoelectronic properties and outstanding biocompatibility, showing broad application potential in fields such as full-view high-definition live-body imaging, flexible quantum dot displays, warm white LED light sources, and full-spectrum catalysis. These applications rely heavily on the multicolor properties of carbon dots, making the development of industrial-scale technologies for multicolor carbon dots crucial.

[0003] Coal, as a common industrial commodity, is not only abundant in reserves but also inexpensive. More importantly, from a microscopic perspective, it is composed of polystyrene (SP). 2 / sp 3 Graphite microcrystals, with hybrid carbon as the main component, are macromolecular polymers formed by three-dimensional cross-linking of short aliphatic and ether bonds. The graphite microcrystals are usually zero-dimensional carbon nanoparticles, similar to the conjugated carbon cores of carbon dots; while the cross-linked bonds that break after exfoliation can provide abundant amorphous surface groups for carbon dots, making coal an ideal raw material for the preparation of carbon dots.

[0004] Currently, the main method for preparing coal-based carbon dots involves using strong oxidants to break and sever the cross-linking bonds between graphite crystallites, releasing them as carbon dots. However, while breaking these cross-linking bonds, the oxidants also indiscriminately oxidize a large number of functional groups and dangling bonds on the surface of the crystallites. This results in fewer surface functional groups in the prepared carbon dots (CDs), leading to fluorescence primarily originating from the carbon core. The small effective conjugated π-domain and large discrete energy band gap in the carbon core result in high fluorescence energy, concentrated in the short-wavelength region, and generally exhibiting a single blue fluorescence. These short-wavelength blue fluorescence signals are susceptible to interference from the autofluorescence of biological tissues, and normal matrix may suffer severe photodamage from short-wavelength irradiation, significantly limiting the application potential of coal-based carbon dots in optoelectronic devices, bioimaging, and other fields, especially in the long-wavelength direction. Summary of the Invention

[0005] The purpose of this invention is to provide a method for preparing sodium-doped coal-based yellow fluorescent carbon dots to solve the problems existing in the prior art.

[0006] To achieve the above objectives, the present invention provides the following solution:

[0007] One of the technical solutions of the present invention: a method for preparing sodium-doped coal-based yellow fluorescent carbon dots, comprising the following steps:

[0008] Bituminous coal was added to a mixed solution of concentrated nitric acid and hydrogen peroxide. After the first mixing reaction, sodium hydroxide was added to adjust the pH to neutral and then a second mixing reaction was carried out to achieve sodium doping, thus obtaining a coal sample.

[0009] The coal sample was added to water to prepare a bituminous coal mixture, and then the bituminous coal mixture was subjected to cavitation stripping treatment to obtain the sodium-doped coal-based yellow fluorescent carbon dots.

[0010] Furthermore, the mass ratio of the bituminous coal to the mixed solution of concentrated nitric acid and hydrogen peroxide is 1:10 to 1:100.

[0011] Furthermore, the mass ratio of the bituminous coal to the mixed solution of concentrated nitric acid and hydrogen peroxide is 1:20-1:25.

[0012] Furthermore, the volume ratio of concentrated nitric acid to hydrogen peroxide is 1:1 to 1:100.

[0013] Furthermore, the rotation speed of the first mixing reaction is 600-1500 r / min, and the time is ≥8h.

[0014] Furthermore, the second mixing reaction is carried out at a rotation speed of 600-1500 r / min for a time of ≥8 h.

[0015] Furthermore, the ratio of coal sample to water is 1-200g:1L.

[0016] Furthermore, the ratio of coal sample to water is 5-50g:1L.

[0017] Furthermore, the cavitation stripping treatment has a flow rate of 10-200 L / h and a time of 5-10 h.

[0018] Furthermore, the cavitation stripping treatment has a flow rate of 25-75 L / h and a duration of 8 h.

[0019] Furthermore, the particle size of the bituminous coal is ≤200 mesh.

[0020] Furthermore, the process includes a filtration step after the second mixing reaction; the filtration includes filtration using a microporous membrane with a pore size of 0.1-0.6 μm.

[0021] Furthermore, the process includes a filtration step to remove large particles after cavitation stripping (i.e., hydrocavitation technology); the filtration includes filtration using a microporous membrane with a pore size of 0.1-0.6 μm.

[0022] The main function of filtration is to remove large coal particles remaining after the reaction, while carbon dots remain in the aqueous solution.

[0023] Furthermore, the cavitation stripping process is carried out in a cavitation device containing a venturi tube.

[0024] The cavitation stripping treatment (i.e., hydraulic cavitation technology) method employed in this invention can effectively sever the cross-linking bonds between graphite microcrystals in coal, releasing them as carbon dots. This method does not require any chemical reagents during cross-linking bond severing, thus avoiding any environmental burden. More importantly, the equipment used is simple and low-cost, making it suitable for large-scale industrial production. Furthermore, unlike chemical methods that sever various cross-linking bonds through redox reactions, this method primarily uses physical actions such as high pressure, shock waves, and microjets to mechanically destroy and sever cross-linking bonds. Therefore, it can retain aliphatic hydrocarbon bonds and ether bonds, as well as other chemical groups, on the carbon dot surface to the maximum extent, thereby enriching the sources of carbon dot fluorescence, primarily through fluorescence induced by surface groups.

[0025] The raw material used in this invention is bituminous coal. The aromatic rings in the structure of bituminous coal are mainly polycyclic, with short side chains, few in number, and few oxygen-containing functional groups. Therefore, a small amount of nitric acid is needed to oxidize and open the aromatic rings, and then a large amount of hydrogen peroxide is used for further oxidation to increase the types and number of oxygen-containing functional groups on the surface of bituminous coal, thus providing a material basis for the subsequent saponification reaction.

[0026] The specific principle is as follows:

[0027] When the bituminous coal mixture flows through a Venturi tube, the cross-section narrows, the flow velocity increases, and the pressure drops below the saturated vapor pressure, causing cavitation nuclei to grow into cavitation bubbles. Upon pressure recovery, some of these cavitation bubbles collapse and release enormous phase transition energy (approximately 1-10 kJ / s) in the form of shock waves (propagation speed 2000 m / s), microjets (high pressure 450 MPa and high shear force 3.5 kPa), thermal effects (generating local hot spots at 2000-6000 K), and chemical effects (primarily generating hydroxyl radicals). 18 kW / m 3 These physical and mechanical actions act on the coal powder, breaking or severing the three-dimensional cross-linking bonds, causing the graphite microcrystals in the coal to be released into the water to form carbon dots.

[0028] In addition, during the pretreatment stage (the first and second mixing reaction stages), the graphite microcrystals in the coal powder are given more oxygen-containing groups, such as carboxyl, hydroxyl, and carbonyl groups, under the combined action of nitric acid and H2O2. After adding NaOH, the original aliphatic hydrocarbon bonds and functionalized -COOR bonds on the surface of the graphite microcrystals undergo a saponification reaction to generate -COONa bonds, thus achieving Na doping of the coal-based carbon dots. Finally, the strong shock wave, high shear force, and microjets generated by hydraulic cavitation are used to peel off the graphite microcrystals and serve as the carbonaceous core of the carbon dots. At the same time, since there is no oxidant, the -COONa bonds generated by the saponification reaction can be retained on the surface of the carbon dots and serve as a key factor in changing the fluorescent band structure of the carbon dots.

[0029] In undoped coal-based carbon dots, the effective conjugated π domain in the carbon nucleus is small, and the discrete energy band gap is relatively large, resulting in high fluorescence energy, which is mostly concentrated in the short-wavelength region and generally appears blue. With Na doping, coal-based carbon dots form new energy bands, the number of energy levels in each band increases, the band gap becomes smaller, the emitted fluorescence energy decreases, and the fluorescence shifts from blue to yellow light.

[0030] The second technical solution of the present invention: a sodium-doped coal-based yellow fluorescent carbon dot prepared by the above preparation method.

[0031] The third technical solution of the present invention: the application of the above-mentioned sodium-doped coal-based yellow fluorescent carbon dots as optoelectronic materials.

[0032] The present invention discloses the following technical effects:

[0033] (1) The present invention has prepared coal-based carbon dots with yellow fluorescence, which breaks through the bottleneck that the fluorescence of coal-based carbon dots is generally blue. It not only extends the fluorescence wavelength of coal-based carbon dots and avoids damage to biological tissues by short-wave radiation, but also expands the color gamut of coal-based carbon dots, which meets the requirements of flexible quantum dot display, warm white LED light source, full-spectrum catalysis and other applications for fluorescence wavelength.

[0034] (2) The preparation method of the present invention has the advantages of low cost, green and environmentally friendly, simple process and operation, and has great potential for continuous industrial production. It can effectively overcome the product quality fluctuation between batches.

[0035] (3) In this invention, the coal sample is first pretreated with a chemical reagent formula (concentrated nitric acid + H2O2 + NaOH) to make it attach yellow fluorescent groups. Then, the graphite microcrystals in the coal are stripped out as CDs by using the mechanical effect generated by the collapse of cavitation while retaining the surface groups.

[0036] (4) By using a combination of concentrated nitric acid, H2O2 and NaOH and controlling the order of addition, the present invention can achieve Na doping on the surface of bituminous coal, thereby changing the band structure of the carbon dots in bituminous coal, achieving a red shift of the fluorescence peak position, and finally obtaining coal-based carbon dots with yellow fluorescence. Attached Figure Description

[0037] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0038] Figure 1Fluorescence curves of the aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in Example 1 under different excitation light and photographs under 365nm ultraviolet light (illustrations);

[0039] Figure 2 High-resolution XPS C1 spectrum of an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in Example 1;

[0040] Figure 3 High-resolution XPS O1 spectrum of an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in Example 1;

[0041] Figure 4 Transmission electron microscope image of sodium-doped coal-based yellow fluorescent carbon dots prepared in Example 1;

[0042] Figure 5 Fluorescence curves of the aqueous solution of coal-based carbon dots prepared for Comparative Example 1 under different excitation light and photographs under 365nm ultraviolet light (inset);

[0043] Figure 6 Fluorescence curves of the aqueous solution of coal-based carbon dots prepared for Comparative Example 2 under different excitation light and photographs under 365 nm ultraviolet light (inset). Detailed Implementation

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0046] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0047] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0048] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0049] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0050] In the specific embodiments of the present invention, the concentration of concentrated nitric acid is 68 wt% and the concentration of hydrogen peroxide is 30 wt%.

[0051] Example 1

[0052] A method for preparing sodium-doped coal-based yellow fluorescent carbon dots:

[0053] (1) Dry 30g of bituminous coal to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample.

[0054] (2) Weigh 20g of raw coal sample, mix the raw coal sample with a mixed solution of concentrated nitric acid and hydrogen peroxide (volume ratio of concentrated nitric acid and hydrogen peroxide is 1:10) at a mass ratio of 1:25, stir at 1500r / min for 8h, add 20g of sodium hydroxide, adjust the pH to neutral, continue stirring at 1500r / min for 8h, filter with a microporous membrane with a pore size of 0.45μm to obtain 15g of treated coal sample.

[0055] (3) Mix 15g of the treated coal sample prepared in step (2) with 1L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0056] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 45 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots.

[0057] The fluorescence curves of the aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in this embodiment under different excitation lights and the photographs under 365nm ultraviolet light (illustrations) are shown below. Figure 1 .

[0058] from Figure 1As can be seen, the carbon dots prepared in this embodiment exhibit yellow fluorescence.

[0059] The high-resolution XPS C1 spectrum of the aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in this embodiment is shown in [reference needed]. Figure 2 High-resolution XPS O1 spectrum can be found Figure 3 .

[0060] from Figure 2 and Figure 3 As can be seen from the data, the carbon dots prepared in this embodiment contain COONa groups, indicating that sodium ions have been successfully doped.

[0061] The aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots prepared in this embodiment was dropped onto a copper mesh containing a film, dried, and then analyzed by transmission electron microscopy. The results are shown in the figure. Figure 4 .

[0062] Example 2

[0063] A method for preparing sodium-doped coal-based yellow fluorescent carbon dots:

[0064] (1) Dry 50g of bituminous coal to constant weight, grind it and pass it through a 400-mesh sieve to obtain a primary coal sample.

[0065] (2) Weigh 30g of initial coal sample, mix the initial coal sample with a mixed solution of concentrated nitric acid and hydrogen peroxide (volume ratio of concentrated nitric acid and hydrogen peroxide is 1:20) at a mass ratio of 1:25, stir at 1500r / min for 8h, add 50g of sodium hydroxide, adjust the pH to neutral, continue stirring at 1500r / min for 8h, filter with a microporous membrane with a pore size of 0.45μm to obtain 26g of treated coal sample.

[0066] (3) Mix 26g of the treated coal sample prepared in step (2) with 2L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0067] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 45 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots.

[0068] Example 3

[0069] A method for preparing sodium-doped coal-based yellow fluorescent carbon dots:

[0070] (1) Dry 30g of bituminous coal to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample.

[0071] (2) Weigh 20g of raw coal sample, mix the raw coal sample with a mixed solution of concentrated nitric acid and hydrogen peroxide (volume ratio of concentrated nitric acid and hydrogen peroxide is 1:30) at a mass ratio of 1:25, stir at 1500r / min for 8h, add 30g of sodium hydroxide, adjust the pH to neutral, continue stirring at 1500r / min for 8h, filter with a microporous membrane with a pore size of 0.45μm to obtain 15g of treated coal sample.

[0072] (3) Mix 15g of the treated coal sample prepared in step (2) with 2L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0073] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 45 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots.

[0074] Example 4

[0075] A method for preparing sodium-doped coal-based yellow fluorescent carbon dots:

[0076] (1) Dry 30g of bituminous coal to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample.

[0077] (2) Weigh 20g of initial coal sample, mix the initial coal sample with a mixed solution of concentrated nitric acid and hydrogen peroxide (volume ratio of concentrated nitric acid and hydrogen peroxide is 1:50) at a mass ratio of 1:25, stir at 1500r / min for 8h, add 30g of sodium hydroxide, continue stirring at 1500r / min for 8h, filter with a microporous membrane with a pore size of 0.45μm to obtain 16g of treated coal sample.

[0078] (3) Mix 16g of the treated coal sample prepared in step (2) with 2L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0079] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 75 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of sodium-doped coal-based yellow fluorescent carbon dots.

[0080] The fluorescence properties of the carbon dots prepared in Examples 2, 3, and 4 are similar to those in Example 1.

[0081] Comparative Example 1

[0082] Preparation of coal-based carbon dots:

[0083] (1) Dry 30g of bituminous coal to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample.

[0084] (2) Weigh 20g of initial coal sample and add it to concentrated nitric acid solution at a mass ratio of 1:25. Stir at 1500r / min for 8h and then add 20g of sodium hydroxide to adjust the pH to neutral. Continue stirring at 1500r / min for 8h. Filter the mixture using a microporous membrane with a pore size of 0.45μm to obtain 17g of treated coal sample.

[0085] (3) Mix 15g of the treated coal sample prepared in step (2) with 1L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0086] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 45 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of coal-based carbon dots.

[0087] The fluorescence curves of the aqueous solution of coal-based carbon dots prepared in this comparative example under different excitation lights and the photographs under 365nm ultraviolet light (illustrations) are shown below. Figure 5 .

[0088] from Figure 5 As can be seen from the data, the fluorescence peak of the carbon dots prepared in this comparative example is located in the blue light region, and the fluorescence also appears blue.

[0089] Comparative Example 2

[0090] Preparation of coal-based carbon dots:

[0091] (1) Dry 30g of bituminous coal to constant weight, grind it and pass it through a 200-mesh sieve to obtain a primary coal sample.

[0092] (2) Weigh 20g of initial coal sample, mix the initial coal sample with a mixed solution of concentrated nitric acid and hydrogen peroxide (volume ratio of concentrated nitric acid and hydrogen peroxide is 1:10) at a mass ratio of 1:25, stir at 1500r / min for 8h, filter with a microporous membrane with a pore size of 0.45μm to obtain 18g of treated coal sample.

[0093] (3) Mix 15g of the treated coal sample prepared in step (2) with 1L of deionized water and stir at 1500r / min for 8h to obtain bituminous coal mixture.

[0094] (4) Place the bituminous coal mixture in a cavitation device equipped with a venturi tube, start the cavitation program, adjust and maintain the flow rate at 45 L / h, collect the circulating liquid in the cavitation device after 8 hours of cavitation stripping, filter it with a microporous membrane with a pore size of 0.45 μm to remove residual large particles, and obtain an aqueous solution of coal-based carbon dots.

[0095] The fluorescence curves of the aqueous solution of coal-based carbon dots prepared in this comparative example under different excitation lights and the photographs under 365nm ultraviolet light (illustrations) are shown below. Figure 6 .

[0096] from Figure 6 As can be seen from the data, the fluorescence peak of the carbon dots prepared in this comparative example is located in the blue light region, and the fluorescence also appears blue.

[0097] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for preparing sodium-doped coal-based yellow fluorescent carbon dots, characterized in that, Includes the following steps: Bituminous coal was added to a mixed solution of concentrated nitric acid and hydrogen peroxide. After the first mixing reaction, sodium hydroxide was added to adjust the pH to neutral, and a second mixing reaction was carried out to obtain a coal sample. The coal sample was added to water to prepare a bituminous coal mixture, and then the bituminous coal mixture was subjected to cavitation stripping treatment to obtain the sodium-doped coal-based yellow fluorescent carbon dots.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the bituminous coal to the mixed solution of concentrated nitric acid and hydrogen peroxide is 1:10 to 1:

100.

3. The preparation method according to claim 1, characterized in that, The volume ratio of concentrated nitric acid to hydrogen peroxide is 1:1 to 1:

100.

4. The preparation method according to claim 1, characterized in that, The rotation speed of the first mixing reaction is 600-1500 r / min, and the time is ≥8h.

5. The preparation method according to claim 1, characterized in that, The second mixing reaction is carried out at a rotation speed of 600-1500 r / min for a time of ≥8 h.

6. The preparation method according to claim 1, characterized in that, The ratio of coal sample to water used is 1-200g:1L.

7. The preparation method according to claim 1, characterized in that, The cavitation stripping process has a flow rate of 10-200 L / h and a duration of 5-10 h.

8. The preparation method according to claim 1, characterized in that, The particle size of the bituminous coal is ≤200 mesh.

9. A sodium-doped coal-based yellow fluorescent carbon dot prepared by the preparation method according to any one of claims 1 to 8.

10. The application of the sodium-doped coal-based yellow fluorescent carbon dots of claim 9 as an optoelectronic material.

Citation Information

Patent Citations

  • Green method for producing mixture of multiple nano-carbon polymorphs from coal

    CN111344252A

  • Method for preparing fluorescent carbon dots by stripping coal gasification slag through hydrodynamic cavitation

    CN118026148A

  • Preparation method of coal-based yellow fluorescent carbon dot aqueous solution

    CN119461338A

  • Process for preparing multicolor, fluorescent carbon quantum dot nanoparticles from coal under mild oxidation conditions

    US20220333011A1